Applied choice analysis : a primer - Hensher, David A., 1947- (Cambridge University Press, 2005)
This primer provides an unintimidating introduction to the main techniques of choice analysis. A companion website provides practice data sets and software to apply all modeling and data skills presented in the book. An invaluable resource to students and of value to anyone else interested in choice analysis and modelling.